(untitled) (Global Journal of Science Frontier Research, 2020)
Urbanization results increased fraction of impervious surfaces, which leads to the generation of pollutants through various anthropogenic activities during dry periods and washout these pollutants during rainfall events that finally enter into the receiving water bodies. This further deteriorate the water quality and unbalance the aquatic ecosystem. Hence, characterization of urban stormwater quality is critically important for selecting a suitable treatment system to safeguard the receiving water sources. The paper focused on the analysis of urban stormwater quality parameters (e.g., pH, turbidity, electric conductivity (EC), suspended solids (SS) and biochemical oxygen demand (BOD) for three different land uses such as residential, commercial and, industrial. The stormwater samples were collected from three different land-use areas in Rajshahi City. The laboratory test results showed that SS, turbidity, EC were found significant for industrial areas where pH and BOD show higher value in residential and industrial areas, respectively. The study results will provide guidelines to the stormwater management authority for the selection of suitable treatment systems to protect the receiving water quality for different land types in Rajshahi city.